Digital skill and digital safety in combating online fraud: A cross-generational study - Nurrahmi, Febri; Nisak , Cut Lusi Chairun; Masykar, Tanzir; Asgha , Ashabul Yamin (Jurnal Komunikasi, 2025)
Aceh reported 1,987 cases of illegal financial activities between November 2024 and May 2025. This study examines the levels of digital skill and digital safety among Gen X, Gen Y, and Gen Z in the context of online fraud. A total of 300 Acehnese respondents aged 17–60 years participated in the study. Data were collected through an online survey using a questionnaire distributed via Google Forms. The data were further analyzed using descriptive statistics and the Kruskal–Wallis test in SPSS version 22. The results showed generational differences in digital skills and digital safety. Gen Y achieved the highest scores in both domains, followed by Gen Z with slightly lower results. At the same time, Gen X consistently reported the lowest. Across all groups, digital safety scores lagged behind digital skill scores. Strengthening digital safety awareness is therefore crucial to reducing vulnerability to online fraud.